Capacity Building of Teachers through ICT in Education Curriculum - Rathnabai S., Angel (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The Digital India Campaign (2015) focusing on the three vision areas: Digital Infrastructure as Core Utility to Every Citizen, e-Governance and Services on Demand and Digital literacy and empowerment of citizens strives to transform India into a digitally empowered society and knowledge economy. The three cardinal principle of the draft New National Education Policy (2016) viz., access, equity and quality could also be served well by harnessing the huge potential of ICT. In this context, ICT intervention at school system to leverage the outcome of education is also a goal. To achieve this goal, human resources i.e., teachers are the game changers and hence the emphasis lies on the capacity building of teachers. National Policy on ICT in Education (2012) also states capacity building of teachers as key to the widespread infusion of ICT enabled practices in the school system. ICT in Education curriculum for teachers becomes the necessity to define the focus, content, strategy for in-service trainings to build capacity of teachers in integrating ICT in Education. This article brings out the features and scope ICT in Education Curriculum for teachers developed by Central institute of Educational Technology (CIET), a constituent unit of National Council of Educational Research and Training (NCERT). This curriculum is being implemented to build the competencies of teachers in integrating content, pedagogy and ICT in teaching and learning. It proposes a blended approach for training integrating face to face and online modes. With this competency based curriculum, it is possible to prepare the teachers to face the expectations of current digital era.